Faktor-Faktor yang Mempengaruhi Kecemasan Ibu Hamil Primigravida Trisemster III dalam Menghadapi Persalinan di Puskesmas Batu Aji Kota Batam Tahun 2018 - Yuditia Prameswari (Psyche 165 Journal, 2019)
The first pregnancy (primigravida) is a very important event for women because in addition to feeling happy and meaningful, it is also possible to feel anxiety and fear, when preparing for labour, especially entering the third trimester. Anxiety and fear can cause pain and can lead to decreased uterine contractions, so the labor process will last longer. The purpose of this study was to determine the factors that influencing the anxiety of Primigravida Trimester III pregnant women, in dealing with childbirth at the Batu Aji Health Center in Batam in 2018. This study was analytical with a cross sectional approach conducted in May - September 2018 at the Batu Aji City Health Center Batam. Data from the Batam City Health Office (Dinas Kesehatan Kota Batam) in 2017 shows that the highest coverage of pregnant women visits is in the Batu Aji Health Center with 4073 pregnant women. The sampling technique is total sampling with a sample size of 40 pregnant women. This study used the HRS-A questionnaire and checklist sheet. The researcher revealed that knowledge, occupational status, age were the factors to be studied. Data analysis using Chi-Square and the results obtained p = 0,000 <0,05, which indicates a significant correlation between the knowledge of pregnant women and anxiety of pregnant women, p = 0,155 <0,05, no correlation between working status and the anxiety of pregnant women, p = 0.571 ≥ 0.05 and there is a correlation between the age of the mother and the anxiety of pregnant women, p = 0.004 <0.050. There were 23 pregnant women who experienced low anxiety (57.7%), 35 people had good knowledge about pregnancy (87.5%). Advice for health workers is to be able to improve the quality of care for pregnant women to reduce anxiety experienced by mothers, and pregnant women should use the health care facilities that have been provided.